Non-dialytic management of sepsis-induced acute kidney injury - Rajapakse, S.; Wijewickrama, E.S. (My University, 2009)
Sepsis is an important cause of morbidity and mortality. Acute Kidney Injury (AKI) often complicates sepsis, leading to greater complexity, higher cost of care and worsening prognosis. Despite the improved understanding of its underlying pathophysiological basis, there have been very few interventions, which have consistently been shown to be of value in the management of sepsis-induced AKI. Measures such as adequate hydration, maintenance of adequate circulating blood volume and mean arterial pressure, and avoidance of nephrotoxins, are still the mainstay of prevention. Loop diuretics, mannitol and "low dose" dopamine have been clearly shown to be of no value in the prevention or treatment of AKI and may, in fact, do harm. Among the remaining pharmacological options, N-acetylcysteine (NAC) may have a role in the prevention of radiocontrast induced AKI.